Attenuation of ROS/Chloride Efflux-Mediated NLRP3 Inflammasome Activation Contributes to Alleviation of Diabetic Cardiomyopathy in Rats after Sleeve Gastrectomy. (19th April 2022) - Li, Songhan; Dong, Shuohui; Shi, Bowen; Xu, Qian; Li, Linchuan; Wang, Shuo; Zhang, Wenjie; Zhong, Mingwei; Zhu, Jiankang; Cheng, Yugang; Zhang, Guangyong; Hu, Sanyuan
Abstract : Diabetic cardiomyopathy (DCM) can develop in diabetes mellitus and is a major cause of morbidity and mortality. Surgical bariatric surgery procedures, such as sleeve gastrectomy (SG), result in remission of type 2 diabetes and have benefits regarding systolic and diastolic myocardial function. The NLR family pyrin domain containing 3 (NLRP3) inflammasome appears to participate in the development of DCM. However, whether SG surgery affects myocardial NLRP3 inflammasome-related pyroptosis to improve cardiac function remains unclear. This study was aimed at investigating the effect of SG surgery on NLRP3-associated pyroptosis in rats with DCM. We also examined cellular phenotypes and molecular mechanisms in high glucose-stimulated myocytes. The rat model of DCM was established by high-fat diet feeding and low-dose streptozotocin injection. We observed a metabolic benefit of SG, including a reduced body weight, food intake, and blood glucose levels and restored glucose tolerance and insulin sensitivity postoperatively. We observed a marked decline in glucose uptake in rats with DCM, and this was restored after SG. Also, SG alleviated the dysfunction of myocardial contraction and diastole, delayed the progression of DCM, and reduced the NLRP3 inflammasome-mediated myocardial pyroptosis in vivo . H9c2 cardiomyocytes showed membrane disruption and DNA damage under a high glucose stimulus, which suggested myocardial pyroptosis. Using a ROS scavenger or chloride channel blocker in vitro restored myocardial NLRP3-mediated pyroptosis. Furthermore, we found that chloride efflux acted downstream of ROS generation. In conclusion, SG may ameliorate or even reverse the progression of DCM. Our study provides evidence that the SG operation alleviates NLRP3 inflammasome dysregulation in DCM. Clearance of ROS overburden and suppression of chloride efflux due to SG might act as the proximal event before inhibition of NLRP3 inflammasome in the myocardium, thus contributing to morphological and functional alleviation of DCM.